Advancements in technologies: new opportunities to investigate factors contributing to differential technology and information use. (12th March 2007) - Workman, Michael
Technology use has been of interest to both practitioners and researchers for over a decade; however, the use of information manipulated and rendered by technologies has been largely ignored. One reason for this has been the difficulty in separating information use from technology use. Historically, information technologies have been rather passive, and merely gathered information to inform a human decision maker, which made it difficult to determine if the technology user made use of the information. Recent advances in expert systems technology have enabled the concurrent investigation of technology and information use because expert systems generate explicit courses of action for users to follow, which can be observed. Using an expert system, this empirical study investigated technology and information use to determine their impact on the organisation.